The future is faster than you think how converging technologies are transforming business, industries, and our lives - Diamandis, Peter H. (New York Simon & Schuster, 2020)
In their book Abundance, bestselling authors and futurists Peter Diamandis and Steven Kotler tackled grand global challenges, such as poverty, hunger, and energy. Then, in Bold, they chronicled the use of exponential technologies that allowed the emergence of powerful new entrepreneurs. Now the bestselling authors are back with The Future Is Faster Than You Think, a blueprint for how our world will change in response to the next ten years of rapid technological disruption.
Includes bibliographical references (pages 271-347) and index.
Keywords: Technological innovations--Economic aspects